Fe-n-s-c single-atom catalyst and application thereof in lithium-sulfur battery separator
Patent Information
- Application Number
- CN202610871870.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-16
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]然而,现有Fe-N-S-C材料的制备过程复杂,且催化活性位点的暴露不足
[0024]1、本发明利用ZIF-8为自牺牲模板,通过离子交换和高温热解,成功制备了具有空心多面体结构的Fe-N-S-C单原子催化剂,方法简便,易于规模化。
Smart Images

Figure CN122999245A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-sulfur battery technology, specifically relating to a method for preparing an Fe-NSC single-atom catalyst and its application in the modification of lithium-sulfur battery separators. Background Technology
[0002] The lithium-sulfur battery has a capacity of 2600 Wh·kg. -1 The theoretical energy density and 1675 mAh·g -1 With its theoretical specific capacity, abundant sulfur resources, and environmental friendliness, lithium-sulfur batteries are considered an important development direction for next-generation high-energy-density energy storage systems. However, the commercial application of lithium-sulfur batteries still faces many challenges: First, the electronic insulation of elemental sulfur and discharge end products (Li2S2 / Li2S) leads to low utilization of active materials; second, during charge and discharge, soluble intermediate lithium polysulfides (LiPSs) easily dissolve in the electrolyte and diffuse through the separator to the lithium anode under the drive of concentration gradient, causing a severe "shuttle effect," resulting in rapid capacity decay and a decrease in coulombic efficiency.
[0003] To suppress the shuttle effect, researchers have developed various strategies, including pore confinement, polar adsorption, and catalytic conversion, in the cathode sulfur host material. In recent years, metal-nitrogen-carbon (MNC) single-atom catalysts have attracted considerable attention due to their atomically dispersed active sites, excellent catalytic activity, and high atom utilization. Studies have shown that Fe-N in Fe-NC materials… X The sites exhibit strong adsorption capacity and catalytic conversion activity for LiPSs, significantly accelerating the redox kinetics of polysulfides. One team synthesized iron-nitrogen co-doped carbon microspheres (Fe-NC) with ultra-high pore volume as a sulfur support, effectively addressing the performance degradation problem caused by lithium polysulfide shuttle. Further research shows that introducing sulfur doping around the Fe-N4 sites can modulate their electronic structure, causing charge density to accumulate around the Fe-NSC configuration, thereby enhancing the adsorption of LiPSs and promoting sulfur conversion.
[0004] However, the preparation process of existing Fe-NSC materials is complex, and the exposure of catalytic active sites is insufficient. Therefore, developing a Fe-NSC material that is easy to prepare, structurally stable, and has high catalytic activity, and applying it to lithium-sulfur battery separators, is of significant research value. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention proposes a Fe-NSC single-atom catalyst and applies it to the modification of lithium-sulfur battery separators. The Fe-NSC material prepared by this method is rich in Fe-N. XThe active sites, through sulfur doping, further regulate their electronic structure, which can effectively adsorb and catalyze the conversion of polysulfides, suppress the shuttle effect, and significantly improve the cycle stability and rate performance of lithium-sulfur batteries.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A Fe-NSC single-atom catalyst is obtained through the following steps:
[0008] Step S1: Prepare a 1.6M 2-methylimidazolium methanol solution and a 0.1M Zn(NO3)2·6H2O methanol solution, respectively. Mix the two solutions at a volume ratio of 1:2–4 and stir vigorously at room temperature for 24 h. Wash with methanol and centrifuge, repeating three times. Dry the collected precipitate under vacuum at 60–80 °C for 12 h to obtain the ZIF-8 template.
[0009] Step S2: Disperse 200 mg ZIF-8 in 20 mL of methanol, and add 0.5–2 mL of Fe(NO3)3·9H2O methanol solution (10 mg·mL). -1 Then add 40-60 mL of 4,4-dihydroxydiphenyl sulfone methanol solution (3.0-4.0 M) and stir at room temperature for 10-20 h. After washing three times with methanol, dry under vacuum at 60-80 °C for 12 h to obtain the Fe-NSC precursor.
[0010] Step S3: Place the precursor in a tube furnace and pyrolyze it at 900℃ for 3 hours under an Ar atmosphere (heating rate 5℃·min). -1 ), thus obtaining the Fe-NSC single-atom catalyst.
[0011] Furthermore, the two solutions described in step S1 are in a volume ratio of 1:2 to 4.
[0012] Furthermore, the centrifugation process described in step S2 involves centrifuging at 8000 rpm for 5 minutes.
[0013] This invention also claims protection for the Fe-NSC single-atom catalyst material obtained by the preparation method described above.
[0014] Furthermore, the Fe-NSC single-atom catalyst is used in the preparation of a lithium-sulfur battery separator modification layer.
[0015] When the Fe-NSC catalyst described in this invention is used for the modification of lithium-sulfur battery separators, the Fe-NSC catalyst, carbon nanotubes (CNTs) and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of (6-8):(1-3):(1-2), and N-methylpyrrolidone (NMP) is added to prepare a uniform slurry. The slurry is then coated on one side of a polypropylene separator, and after drying, the Fe-NSC modified separator is obtained.
[0016] Furthermore, the loading of the Fe-NSC catalyst on the membrane is 0.1–0.5 mg·cm⁻¹. -2 .
[0017] The application of the Fe-NSC catalyst described in this invention in the preparation of sulfur host material for lithium-sulfur battery cathode involves mixing the Fe-NSC catalyst with elemental sulfur at a mass ratio of 3:7 and melting and diffusing at 155°C for 12 hours to obtain S@Fe-NSC composite cathode material.
[0018] The Fe-NSC catalyst described in this invention benefits from the following mechanism when used for electrocatalytic polysulfide conversion:
[0019] 1. Fe-N X There are strong Li-N and Fe-S interactions between the active sites and LiPSs, which can effectively adsorb soluble polysulfides and inhibit the shuttle effect;
[0020] 2. Fe-N X Sulfur doping around the active site modulates the electronic structure of the Fe center, causing the charge density to accumulate around the Fe-NSC configuration and enhancing the catalytic activity;
[0021] 3. Fe-N X The active sites and Fe3C nanoparticles synergistically catalyze the conversion of polysulfides, accelerating the conversion of S8. LiPSs Redox kinetics of Li2S2 / Li2S;
[0022] 4. The N and S co-doped carbon matrix provides a good electronic conductivity network, which promotes interfacial charge transfer.
[0023] The present invention has the following beneficial effects:
[0024] 1. This invention utilizes ZIF-8 as a self-sacrificing template to successfully prepare Fe-NSC single-atom catalysts with hollow polyhedral structures through ion exchange and high-temperature pyrolysis. The method is simple and easy to scale up.
[0025] 2. This invention modulates the electronic structure of the single-atom Fe center by introducing sulfur doping around the Fe-N4 site, thereby enhancing the adsorption capacity and catalytic conversion activity of polysulfides.
[0026] 3. The Fe-NSC catalyst prepared by this invention contains atomically dispersed Fe-N X The active sites and Fe3C nanoparticles produce a synergistic catalytic effect, accelerating the conversion kinetics of polysulfides.
[0027] 4. Lithium-sulfur batteries assembled with Fe-NSC modified separators exhibit excellent rate performance and cycle stability. Attached Figure Description
[0028] Figure 1 The image shows the XRD pattern of the Fe-NSC catalyst prepared in Example 1.
[0029] Figure 2 The image shows the Raman spectrum of the Fe-NSC catalyst prepared in Example 1.
[0030] Figure 3 The image shows the XPS spectrum of the Fe-NSC catalyst prepared in Example 1.
[0031] Figure 4 The high-resolution N1s spectrum fitting effect of the Fe-NSC catalyst prepared in Example 1 is shown.
[0032] Figure 5 The capacity retention rate of the Fe-NSC catalyst prepared in Example 3 after 100 cycles at 0.2C. Detailed Implementation
[0033] The following specific embodiments of the present invention will provide a detailed and comprehensive description of the technical solutions of the present invention. It should be noted that the provided embodiments represent only a part of the present invention, and not all of it. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0034] Unless otherwise specified, the experimental methods used in the embodiments of this invention are all conventional methods; unless otherwise specified, the materials and reagents used are commercially available reagents and materials, and the commercially available raw materials are used to remove insoluble matter and other impurities by general filtration methods.
[0035] Example 1
[0036] Step S1: Prepare a 1.6M 2-methylimidazolium methanol solution and a 0.1M Zn(NO3)2·6H2O methanol solution. Mix the two solutions at a volume ratio of 1:3 and stir vigorously at room temperature for 24 hours. Wash with methanol and centrifuge, repeating three times. Then, dry the collected precipitate under vacuum at 70°C for 12 hours to obtain ZIF-8.
[0037] Step S2: Disperse 200 mg of ZIF-8 in 20 mL of methanol, then inject 1 mL of Fe(NO3)3·9H2O methanol solution (10 mg·mL). -1 Add 50 mL of 4,4-dihydroxydiphenyl sulfone methanol solution (3.2 M) to the above dispersion and stir at room temperature for 15 h. Wash three times with methanol and then vacuum dry at 70 °C for 12 h to obtain the Fe-NSC precursor.
[0038] Step S3: The Fe-NSC precursor was placed in a tube furnace and pyrolyzed at 900℃ for 3 hours under a flowing Ar atmosphere (heating rate 5℃·min). -1 ), thus obtaining the Fe-NSC single-atom catalyst.
[0039] The results of the Fe-NSC catalyst in Example 1 show that after high-temperature treatment, the Fe-NSC catalyst still retains the ZIF-8 derived polyhedral shape, with a particle size of approximately 200-500 nm. Elemental mapping images show that C, N, S, and Fe elements are uniformly distributed within the particles. XRD patterns show two diffraction peaks at 2θ = 25° and 44°, corresponding to the (002) and (101) crystal plane characteristic diffractions of graphitic carbon, respectively. Raman spectroscopy shows a D peak (~1350 cm⁻¹). -1 ) and G peak (~1580 cm) -1 This indicates the presence of graphitized structures and defect sites in the material. XPS full-spectrum analysis confirmed the coexistence of Fe, N, S, and C in the Fe-NSC catalyst, while high-resolution N 1s spectra showed the simultaneous presence of pyridine-N, pyrrole-N, graphitic-N, and Fe-N. x Characteristic peaks confirm Fe-N X The active site was successfully constructed. Furthermore, no Fe or Fe2+ was observed in the XRD pattern. X The C diffraction peaks indicate that Fe has not formed a distinct crystalline phase; the D / G peaks in the Raman spectrum indicate defects in the carbon matrix, which is beneficial for anchoring single atoms; and a clear Fe-N phase was detected in the XPS high-resolution N 1s spectrum. X Characteristic peaks confirm that Fe is coordinated with N. Combined data indicates a single-atom configuration.
[0040] Example 2
[0041] Preparation of Fe-NSC catalyst-modified membrane: The Fe-NSC catalyst prepared in Example 1, carbon nanotubes (CNTs), and polyvinylidene fluoride (PVDF) were mixed at a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added to prepare a homogeneous slurry. This slurry was coated onto one side of a commercial polypropylene (PP) membrane (Celgard 2400) using a blade coating method, with a coating thickness of approximately 20 μm. The membrane was then vacuum-dried at 60 °C for 12 h to obtain the Fe-NSC modified membrane. The catalyst loading on the membrane was calculated to be approximately 0.25 mg·cm³. -2 .
[0042] The results of the Fe-NSC modified membrane in Example 2 showed that the coating was uniformly covered on the surface of the PP membrane, with no obvious cracks or agglomeration. The coating thickness was about 20 μm, and it bonded well with the PP membrane substrate.
[0043] Example 3
[0044] Lithium-sulfur battery assembly and testing:
[0045] Cathode preparation: Elemental sulfur and the Fe-NSC catalyst prepared in Example 1 were mixed and ground at a mass ratio of 7:3, and then melt-diffused at 155℃ under an argon atmosphere for 12 h to obtain the S@Fe-NSC composite material. The S@Fe-NSC composite material, CNT, and PVDF were mixed in NMP at a mass ratio of 7:2:1 and homogenized. The mixture was then coated onto a carbon-coated aluminum foil (15 μm), vacuum dried at 60℃ for 12 h, and cut into discs with a diameter of 12 mm. The sulfur loading was approximately 1.2-1.5 mg·cm³. -2 .
[0046] Battery Assembly: CR2032 coin cells were assembled in an Ar atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm). Lithium metal sheets were used as the negative electrode, and the Fe-NSC modified separator prepared in Example 2 was used as the separator. The S@Fe-NSC composite positive electrode was used as the positive electrode. The electrolyte consisted of 1 M LiTFSI and 1% LiNO3 in a 1:1 V / V solution of 1,3-dioxane (DOL) and dimethoxymethane (DME).
[0047] Electrochemical testing: Constant current charge-discharge tests were performed using a Neware battery testing system, with a voltage range of 1.7-2.8V. Rate performance testing involved 5 cycles each at 0.1C, 0.2C, 0.5C, 1C, and 2C, followed by testing at 0.2C. Cycling performance testing was conducted at 0.5C. Electrochemical impedance spectroscopy was measured in the frequency range of 0.01-100 kHz on the same ivium electrochemical workstation.
[0048] The lithium-sulfur battery assembled in Example 3 had an initial discharge specific capacity of 1380 mAh·g at a 0.1C rate. -1 It is close to the theoretical specific capacity of sulfur. The initial discharge specific capacity at 0.5C rate is 1156 mAh·g. -1 After 300 cycles, the capacity retention rate was 86.5%, and the average coulombic efficiency was higher than 99%. It still maintained 680 mAh·g at a high rate of 2C. -1 The specific capacity was [not specified]. EIS test results showed that the interfacial charge transfer resistance (Rct) of the battery assembled with Fe-NSC modified separator was approximately 35Ω, significantly lower than that of the blank separator battery (approximately 80Ω), indicating that the modified separator effectively reduced the interfacial impedance.
[0049] Example 4
[0050] The difference between this embodiment and Example 3 is that the sulfur host material in this embodiment is a single nitrogen-doped carbon material (unloaded Fe-NSC), while the separator is still the Fe-NSC modified separator prepared in Example 2. The sulfur loading and other assembly conditions remain unchanged.
[0051] Electrochemical test results show that the initial discharge specific capacity at 0.2C rate is 1150 mAh·g. -1 After 200 cycles at 0.5C, the capacity retention rate was 78.2%. The results show that the Fe-NSC modified separator can effectively suppress the shuttle effect and improve battery performance even in the absence of a catalytic cathode host material.
[0052] Comparative Example 1
[0053] The difference between this comparative example and Example 3 is that the diaphragm used is an unmodified commercial PP diaphragm (Celgard 2400), and the positive electrode uses an S@Fe-NSC composite material.
[0054] Electrochemical test results show that the initial discharge specific capacity at 0.2C rate is 1050 mAh·g. -1 After 200 cycles at a 0.5C rate, the capacity retention was only 52.3%, and the coulombic efficiency fluctuated significantly. The results indicate that the unmodified PP membrane cannot effectively suppress polysulfide shuttle, leading to rapid capacity decay.
[0055] Comparative Example 2
[0056] The difference between this comparative example and Example 3 is that the membrane used is an Fe-NC (without sulfur doping) modified membrane, which is prepared in accordance with Example 2 but uses a sulfur-free precursor.
[0057] Electrochemical test results show that the initial discharge specific capacity at 0.5C rate is 1020 mAh·g. -1After 300 cycles, the capacity retention was 72.4%, lower than the 86.5% of the Fe-NSC modified membrane in Example 3. The results indicate that sulfur doping plays a crucial role in optimizing the electronic structure of the Fe-N4 active sites and enhancing catalytic activity.
[0058] The above embodiments demonstrate that the Fe-NSC single-atom catalyst prepared by this invention possesses the following excellent properties:
[0059] 1. Atomic-scale dispersed Fe-N in Fe-NSC catalyst X The active sites and sulfur doping work synergistically to enhance the adsorption and catalytic conversion capabilities of polysulfides;
[0060] 2. The Fe-NSC modified separator effectively suppresses the shuttle effect and significantly improves the cycle stability of lithium-sulfur batteries;
[0061] 3. Fe-NSC can be used as a sulfur host material to construct composite cathodes, or it can function independently as a membrane modification layer.
[0062] Obviously, the above embodiments of the present invention are merely examples to clearly illustrate the technical solution of the present invention, and are not intended to limit the specific implementation of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the claims of the present invention should be included within the protection scope of the claims of the present invention.
Claims
1. The application of a Fe-NSC single-atom catalyst in the modification of lithium-sulfur battery separators, characterized in that, The Fe-NSC single-atom catalyst is prepared by the following steps: S1. Prepare 1.6M 2-methylimidazolium methanol solution and 0.1M Zn(NO3)2·6H2O methanol solution respectively. Mix the two solutions at a volume ratio of 1:2 to 4, stir at room temperature for 24 hours, and obtain ZIF-8 template after washing, centrifugation and drying. S2. Disperse ZIF-8 in methanol, add Fe(NO3)3·9H2O methanol solution, then add 4,4-dihydroxydiphenyl sulfone methanol solution, stir at room temperature for 10-20 h, and obtain Fe-NSC precursor after washing and drying; S3. The precursor is pyrolyzed at 800-1000℃ under an inert atmosphere to obtain the Fe-NSC single-atom catalyst.
2. The application according to claim 1, characterized in that, The volume ratio of the two solutions in step S1 is 1:2~4.
3. The application according to claim 1, characterized in that, The concentration of the Fe(NO3)3·9H2O methanol solution in step S2 is 10 mg·mL. -1 The amount added is 0.5-2 mL; the concentration of the 4,4-dihydroxydiphenyl sulfone methanol solution is 3.0-4.0 M, and the amount added is 40-60 mL.
4. The application according to claim 1, characterized in that, The heating rate of the pyrolysis in step S3 is 2~6℃·min. -1 The pyrolysis time is 2 to 4 hours.
5. The application according to claim 1, characterized in that, The Fe-NSC single-atom catalyst, carbon nanotubes, and binder are mixed in a mass ratio of (6-8):(1-3):(1-2), added to a solvent to form a slurry, and the slurry is coated on the surface of the separator to assemble a lithium-sulfur battery modified separator.
6. The application according to claim 5, characterized in that, The adhesive is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.
7. The application according to claim 5, characterized in that, The loading of the Fe-NSC single-atom catalyst on the membrane is 0.1–0.5 mg·cm⁻¹. -2 .
